1994
DOI: 10.1523/jneurosci.14-05-02893.1994
|View full text |Cite
|
Sign up to set email alerts
|

Basal cortisol levels and cognitive deficits in human aging

Abstract: A group of 19 healthy elderly subjects previously shown to differ in terms of their cortisol levels over a 4 year period were administered a neuropsychological test battery assessing memory, attention, and language. Correlational analyses performed on various corticosteroid measures showed that the slope of the change in cortisol levels over time predicted cognitive deficits in this elderly population. Aged subjects showing a significant increase in cortisol levels with years and with high current basal cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
295
2
10

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(331 citation statements)
references
References 93 publications
24
295
2
10
Order By: Relevance
“…The results suggest that although most of the association between TSH and cognitive abilities may be due to shared change variation, TSH may exert a direct impact on episodic memory. It is suggested that the mechanism for such effects are increased cortisol levels, known to affect episodic memory functioning in particular (Lupien et al, 1994;van Haasteren et al, 1996). In order to further clarify this topic, it is necessary to expand the age range under scrutiny to cover both younger and older participants, and to add indicators of both relevant thyroid indexes (TSH and thyroxine), and steroid hormone levels.…”
Section: Longitudinal Evidence 22mentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that although most of the association between TSH and cognitive abilities may be due to shared change variation, TSH may exert a direct impact on episodic memory. It is suggested that the mechanism for such effects are increased cortisol levels, known to affect episodic memory functioning in particular (Lupien et al, 1994;van Haasteren et al, 1996). In order to further clarify this topic, it is necessary to expand the age range under scrutiny to cover both younger and older participants, and to add indicators of both relevant thyroid indexes (TSH and thyroxine), and steroid hormone levels.…”
Section: Longitudinal Evidence 22mentioning
confidence: 99%
“…More specifically, low TSH levels are also associated with elevated steroid hormone levels within the hypothalamus-pituitary-adrenal axis (van Haasteren et al, 1996). Increased levels of cortisol, which is part of this circuitry, may result in hippocampal cell loss and impair episodic memory performance (Lupien et al, 1994). Therefore, although thyroid hormones may be associated with a variety of cognitive abilities, there might be a particularly strong link to episodic memory.…”
mentioning
confidence: 99%
“…The reasons for these differences are likely to relate to individual differences in brain aging and in the differences in the distribution of aging, impaired individuals in populations of animals and human subjects (89). Particularly useful have been studies of basal cortisol levels and cognitive deficits in human aging (78,79). Aged subjects followed over a 4-year period, who showed a significant increase in cortisol levels over the 4 years and had high basal cortisol levels in year 4, showed deficits on tasks measuring explicit memory as well as selective attention compared to subjects with either decreasing cortisol levels over 4 years or subjects with increasing basal cortisol but moderate current cortisol levels (78).…”
Section: The Hippocampus and Hpa Regulationmentioning
confidence: 99%
“…For the hippocampus, as well as for the rest of the body, additional information is needed regarding both cognitive function and stress mediators (i.e., HPA and sympathetic nervous system reactivity), as well as measures of body function that are influenced by these mediators (89,91). This is true not only for animal models (96) but also for studies on humans, for which longitudinal information about HPA activity and other measures of allostatic load (91) in aging subjects has been shown to predict cognitive decline and onset of cardiovascular disease (78,79,131). Thus, the most meaningful studies have been done comparing cognitively impaired and unimpaired groups of aging individuals.…”
mentioning
confidence: 99%
“…Many studies have found an age-associated increase in HPA activity (Van Cauter et al, 1996), resulting in elevated cortisol levels (Lupien et al, 1994;Ferrari et al, 1995;Deuschle et al, 1997) and attenuation, or a flattening, of cortisol diurnal rhythm (van Coevorden et al, 1991) suggesting age-dependent HPA axis dysregulation. Additionally, it has long been speculated that chronic elevations of stress-related hormones such as cortisol can weaken multiple physiological systems of older adults resulting in impaired cardiovascular and immune function, as well as contributing to dementia, and mood and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%